2007
DOI: 10.1182/blood.v110.11.4733.4733
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Cancer Testis Antigens Expression in Advanced Stage Multiple Myeloma Patients.

Abstract: Background: Cancer testis antigens have become the most extensively studied antigen group in the field of tumor immunology. Aims: This study aims to analyze global expression of 14 CT (cancer/testis) antigens in MM to identify possible prognostic markers and therapeutic targets. Patients and Methods: The expression of MAGEA1, MAGEA2, MAGEA3/6, MAGEA4, MAGEA10, MAGEA12, BAGE1, MAGEC1/CT7, GAGE family, LAGE-1, PRAME, NY-ESO-1, SPA17 and SSX1 was studied by RT-PCR in: 15 normal tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 21 publications
4
62
0
6
Order By: Relevance
“…8,11 While PRAME expression has been reported as a predictor of both poorer and better patient outcome (e.g. in breast cancer and promyelocytic leukemia, respectively), 34,45,46 it had no influence on survival in our cohort of HNSCC patients. We are the first to report the extent of HERV-K-MEL expression in a large series of HNSCC tumors.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…8,11 While PRAME expression has been reported as a predictor of both poorer and better patient outcome (e.g. in breast cancer and promyelocytic leukemia, respectively), 34,45,46 it had no influence on survival in our cohort of HNSCC patients. We are the first to report the extent of HERV-K-MEL expression in a large series of HNSCC tumors.…”
Section: Discussionmentioning
confidence: 60%
“…32 Caution however must be applied in interpreting positive 57B staining as MAGE-A4 positivity, as the antibody can also recognize other MAGE-A proteins. 17,18 Expression of other CT genes has also been generally associated with poor prognosis, 24,33,34 with only few studies revealing a positive effect. 27,35 None of the CT genes tested in this study was associated with better survival.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer/testis antigens (CTAs) belong to a group of proteins that are expressed in the developing embryo, are restricted to the testis in the adult, and are aberrantly re-expressed in malignancy, particularly high-grade and advanced-stage tumours, including TNBC. [23][24][25][26][27][28] Members of the melanomaassociated antigen (MAGE) family and New York Esophageal Squamous Cell Carcinoma-1 (NY-ESO-1) are among the CTAs being actively investigated as cancer immunotherapy targets. They have been shown to evoke spontaneous cytotoxic T-cell responses in melanoma, oesophageal carcinoma, bladder cancer, and non-small-cell lung carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…A pilot study published in 2016 by South African scientists investigated the possibility of detecting CMCs by their expression of cancer testis antigen MAGE C1 in peripheral blood. The expression of MAGE C1 had been found in the 85%-100% of BM PCs of patients with symptomatic MM (Andrade et al, 2008;Tinguely et al, 2008), but its presence was demonstrated in PB on early stem cell immature B lymphocyte of all patients with symptomatic MM, as well as in the clonal PCs compartment (Shires, Teuchert, Wienand, Shankland, & Novitzky, 2016;Wienand & Shires, 2015). Using MFC (CD34/CD19/ CD45/MAGE C1, and CD138/CD45/MAGE C1) and qRT-PCR techniques (primers and probes for the amplification of MAGE C1), they suggested a valuable tool to routinely monitor clonal malignant progenitor cells destined to feed the progression of the disease.…”
Section: Mfc To Detect Circulating Myeloma Cells In the Peripheral mentioning
confidence: 99%